Billedets begær eller: hvad vil Mitchell? - Bruhn, Jørgen (K&K - Kultur og Klasse, 2007)
W.J.T. Mitchell: What Do Pictures Want. The Lives and Loves of Images, Chicago og London 2005 (The University of Chicago Press).